Customers that count how to build living relationships with your most valuable customers - Cram, Tony (Financial Times Prentice Hall, 2001)
A wonderfully fresh look at CRM. Customers that Count starts with the theses that the nature of human relationship provides a model for creating business loyalty, then reviews important rules of friendship that will help you to build customer relationships. Filled with lots of valuable case histories, this is an idea-a-minute read.' Frederick Newell, author of The New Rules of Marketing Securing repeat business from good customers through long-term loyal relationships is the key to generating profit. However, there are two key elements to this that most people ignore or misunderstand. First, the notion of 'good customers'. That means you have to concentrate on customers that count; the ones who deliver profits. Equally importantly, it means that you should learn to sack 'bad customers'; the others who are destroying value. Second, the notion of 'loyal relationships'. A loyal relationship is one that lives and goes beyond the database. If you want these customers loyalty, you have to treat them like valued human beings, not just numbers. This book is more than just another book on CRM. It goes beyond the concept of capturing cutomers into captivating them. In a world where consumer choice has never been greater, and where the cost of acquiring new customers is sometimes more than the value they bring in, you cant afford to treat all customers the same - the company that seems human will win. As customer value replaces cost control as the guiding principle of management, Tony Cram reveals how to manage the customers that count.